The freedom to wear religious clothing in the case law of the European Court of Human Rights: an appraisal in the light of states' positive obligations - Ferri, Marcella (Religion, state & society, 2017)
This contribution gives an overview of the interpretation elaborated by the European Court of Human Rights of the freedom of thought, conscience and religion (Article 9), paying special attention to the wide case law on the freedom to wear religious symbols and clothing. The analysis is developed in the light of the doctrine of positive obligations, according to which states have some positive obligations requiring them to take the measures necessary to assure the effective implementation of individuals' human rights. Contrary to other rights secured by the European Convention of Human Rights, the European case law on positive obligations flowing from the right to freedom of thought, conscience and religion is rather underdeveloped. This aspect is deeply linked with a notion of religious pluralism which the Court defines in a narrow and excluding way.